PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN BUNGA ARTIFICIAL PADA PT BOTANICAL DECOR SENTOSA DI KABUPATEN TANGERANG - Arifah Dhiya Syifa; Ahmad Nurhadi (Journal of Research and Publication Innovation, 2025)
This study aims to find out how much product quality and service quality affect customer satisfaction at PT Botanical Decor Sentosa in Tangerang Regency, both partially and simultaneously. The method used is quantitative. The data collection method in this study is by manually and online questionnaires to customers of PT Botanical Decor Sentosa in Tangerang Regency.The research population is 165,647 respondents. The test results and samples in this study amounted to 100 respondents. The results of the partial test (t-test) between product quality and customer satisfaction showed a t-value of 7.799 > t table 1.985, for the variable of service quality on customer satisfaction showed a t-value of 4.223 > t table 1.985, while the two variables were tested simultaneously (F test) and obtained the result of the F value of 111.134 > F table 4.83.Simple linear regression obtained the regression equation of the product quality variable is Y=11.674 + 0.712X1. The simple regression service quality variable is Y=11.706 + 0.712X2. Meanwhile, multiple linear regression yields the equation Y=6.445 + 0.523X1 + 0.319X2. The results of the partial correlation of the product quality variable were 0.800, the quality of service was 0.711. The result of simultaneous correlation was 0.834. Meanwhile, the coefficient of determination (R) obtained as a result of product quality and service quality affecting customer satisfaction by 0.696 or 69.6%. While the remaining (100-69.6) 30.4% is influenced by other factors or variables that are not studied in this study. From these results, it can be concluded that product quality and service quality have a positive and significant influence on customer satisfaction.